Primary malignant melanoma of the esophagus: A retrospective analysis of clinical features, management, and survival of 76 patients. Issue 4 (12th March 2019) - Wang, Xuan; Kong, Yan; Chi, Zhihong; Sheng, Xinan; Cui, Chuanliang; Mao, Lili; Lian, Bin; Tang, Bixia; Yan, Xieqiao; Si, Lu; Guo, Jun
Abstract : Background: Primary malignant melanoma of the esophagus (PMME) is rare. Patients with advanced melanoma of esophageal origin tend to have lower response rates to traditional therapies than those with other melanomas. We report our experience of 12 patients with PMME administered PD‐1 inhibitors. Methods: This is a retrospective analysis of the clinical data of 76 patients with PMME who attended Peking University Cancer Hospital between January 2008 and September 2017. Objective response rates (ORRs) and progression‐free survival (PFS) were assessed. Results: The 76 PMMEs were classified as unresectable or metastatic. The patients were allocated to three cohorts according to their treatment: chemotherapy (C: 46 patients), targeted therapy (T: 2 patients), and PD‐1 inhibitors (IT: 12 patients). The PFS in the C cohort was three months with a limited ORR of 10.9%. In the IT cohort, seven patients (75.0%) achieved a partial response and three had stable disease for 4+ months. The median PFS in the IT cohort was not reached and the mean was 15.6 months, which was much longer than in cohort C ( P < 0.001). Conclusion: Although this cohort of patients was small, it is the largest series investigated thus far. To the best of our knowledge, this is the first report of the outcomes of advanced PMMEs treated with PD‐1 inhibitors. Dramatic responses can occur in patients with advanced PMMEs.